Stochastic Filtrate of Essential Workers to Reactivate the World Economy Safely - Manjarrez, Elias; Olmos, Roberto; Cedillo, Lilia; Salazar-Ibarguen, Humberto A. (Frontiers in Physics, 2020)
Because there is a rapidly emerging risk that essential supply chains could collapse during the COVID-19 pandemic, new strategies are urgently needed by governments to protect workers regardless of whether or not they have symptoms. We propose a “stochastic filtrate” of such workers to reduce the risk of physical interactions with workers infected with SARS-CoV-2. Here, we suggest the random real-time-RT-PCR test of SARS-CoV-2 as a filtrating agent, although other more useful tests developed in the future to detect SARS-CoV-2 could also be used instead. Such a focused strategy, when combined with other preventive measures, could be successfully replicated in many countries to reactivate the world's economy safely. Our stochastic filtrate concept includes a mathematical framework and conceptual model. The simulations of this stochastic filtrate process support its viability.